An evaluation of prescribing practices for community-acquired pneumonia (CAP) in Mongolia - Dorj, Gereltuya; Hendrie, Delia; Parsons, Richard; Sunderland, Vivian (BioMed Central, 2013)
BACKGROUND: Community-acquired pneumonia (CAP) is a significant cause of morbidity and mortality in all age groups worldwide. It may be classified as mild/moderate or severe, the latter usually requiring hospitalisation. Although, there are many studies reported in relation to CAP, there is relatively little known about the treatment of CAP and its antibiotic use in Mongolia. The study aim was to evaluate prescribing practices for the treatment of mild/moderate CAP in Mongolia with respect to national prescribing guidelines. METHODS: Written prescriptions with a written diagnosis of CAP included were collected prospectively and sequentially for ten weeks from a purposefully selected sample of community pharmacies in rural and urban areas of Mongolia. The data collected included the patient's age, gender, medication details, frequency and number of doses prescribed. Evaluation was with respect to the Mongolian Standard Treatment Guidelines (2005, 2008). Statistical differences between groups were tested using the Chi-squared and Fisher's exact tests.RESULTS: Prescriptions were collected from 22 pharmacies and represented the prescribing practices of 118 doctors. The study enrolled 394 (193 adults and 201 children) patients, with a median age for children of 2.0 years (range: 0.03-12) and adults of 33.0 years (range: 13--92).The most commonly prescribed drugs were amino penicillins, vitamins, and mucolytics, with the median number of drugs being three per prescription. Inappropriate drug selection was similar for adults (57.7%) and children (56.6%), and the major reason for an overall frequency of inappropriate prescribing for adults were 89.0% and for children 78.0%. Doctors in urban areas prescribed more inappropriate drugs than those in rural areas for both children and adults, p = .0014. The proportion of prescribed injections was 28.4% for adults and 9.0% for children, and for adults was significantly higher in urban areas. The prescribing standard for non-hospitalized patients in Mongolia states that injections should not be prescribed. CONCLUSIONS: The high level of inappropriate prescribing for mild/moderate CAP highlights the need to develop comprehensive and reliable procedures nationwide to improve prescribing practices in Mongolia.